Can AI Improve Medication Adherence Through Digital Tools? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2019)
Medication non-adherence is a critical and pervasive challenge in modern healthcare, contributing to suboptimal clinical outcomes and escalating healthcare c...
Keywords: Telemedicine and Digital Health; Improve; Medication; Adherence; Artificial Intelligence; Machine Learning; Healthcare